2017
DOI: 10.1038/s41467-017-00951-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced nanochannel translocation and localization of genomic DNA molecules using three-dimensional nanofunnels

Abstract: The ability to precisely control the transport of single DNA molecules through a nanoscale channel is critical to DNA sequencing and mapping technologies that are currently under development. Here we show how the electrokinetically driven introduction of DNA molecules into a nanochannel is facilitated by incorporating a three-dimensional nanofunnel at the nanochannel entrance. Individual DNA molecules are imaged as they attempt to overcome the entropic barrier to nanochannel entry through nanofunnels with vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 39 publications
1
62
0
Order By: Relevance
“…These experiments and simulations provided key insight into how polymer stretching is induced by single and multiple collisions and interaction events with stationary posts. The field of electrophoretic DNA manipulation continues to be vibrant today, as reviewed in an extensive article in 2010[26], with recent work showing that nanofabricated 'funnels' can be used to enhance the translocation and localization of genomic DNA in small devices[144].IV. DILUTE SOLUTION LINEAR POLYMER DYNAMICS: 2007 TO PRESENT Major advances in the field of single polymer dynamics have occurred over the last decade.…”
mentioning
confidence: 99%
“…These experiments and simulations provided key insight into how polymer stretching is induced by single and multiple collisions and interaction events with stationary posts. The field of electrophoretic DNA manipulation continues to be vibrant today, as reviewed in an extensive article in 2010[26], with recent work showing that nanofabricated 'funnels' can be used to enhance the translocation and localization of genomic DNA in small devices[144].IV. DILUTE SOLUTION LINEAR POLYMER DYNAMICS: 2007 TO PRESENT Major advances in the field of single polymer dynamics have occurred over the last decade.…”
mentioning
confidence: 99%
“…Noise was also accumulated along a conduit channel. Anyhow, number of theoretical studies of DNA sequencing in nanochannel model continued to study and demonstrated its potential toward DNA sequencing [75][76][77]. Nano funnel structure integrated with nanochannel was also proposed to facilitate the DNA translocation as it can suppress the electric field effect onto the DNA [77].…”
Section: Transverse Electronic Currentmentioning
confidence: 99%
“…Nanofluidics is a branch of fluid mechanics that deals with fluid flow and transport phenomena through nanoscale geometries and has lots of applications in medicine, biology, genetics, material science, and energy conversion technologies . Electrokinetic phenomena are wildly used in nanofluidic devices to perform many tasks such as generating flow field in nanochannels , transport of ions , and manipulating DNAs in the nanoconfinements . The electrokinetics will also affect cell membrane transport through natural or artificial nanopores created on cell membranes .…”
Section: Introductionmentioning
confidence: 99%